Occupational safety and health management in Malaysia: An overview - Chew Abdullah, Nor Azimah; Spickett, Jeffery T.; Rumchev, Krassi B.; Dhaliwal, Satvinder S. (2008)
In today’s economy, globalization has shown tremendous impact on companies. Global competition increases safety and health risks and companies incurred additional cost on safety. To meet the challenges posed by these changes, revamping safety and health practices through strategies to improve performance is critical so as to motivate workforce in creating a safe and healthy environment that lead to decrease work-related accidents and ill-health in the workplace. Although work-related accidents and ill-health are preventable, there is a need for collaboration at the international, regional, national and enterprise levels to accomplish this mission with a positive commitment amongst all concerned. Due to that fact, companies need to focus on continual improvement of their performance in order to survive in the marketplace. One of the mean to encourage employers to achieve a higher standard of safety and health in the workplace is through effective occupational safety and health management.